Rainwater Use Process of Caragana intermedia in Semi-Arid Zone, Tibetan Plateau - Zhu, Yajuan; Wang, Guojie (Frontiers in Earth Science, 2020)
Summer rain is changeable in the semi-arid climate, and is the limiting factor to the survival and growth of sand-fixing vegetation, especially in Tibetan Plateau. Caragana intermedia is the dominant sand-binding shrub on sand dune in the northeast Tibetan Plateau. Stable hydrogen and oxygen isotope of xylem water, soil water, and groundwater were examined to study rainwater uptake process by C. intermedia in mid-summer. Soil water content was monitored continuously before and after a 13.9 mm rain. Contribution of each water source was analysed by MixSIAR model. The results showed surface soil water (0-10 cm) was replenished by rainwater through increasing soil water content and reducing its stable isotope. Caragana intermedia mainly used surface soil water (0-10 cm) replenished by rainwater one day after the rain, accounting for about 60% of its total water source. As water availability decreased in upper soil layers, it used soil water at deeper levels (10-150 cm), the same water source as one day before the rain. The rapid and efficient uptake of rainwater by C. intermedia reflected its response to summer rain, which is an adaptive strategy to the semi-arid environment. Therefore, C. intermedia could survive on sand dune by shallow soil water replenished from rainwater in Tibetan Plateau.